Analysis of Diet Compliance and Physical Activity with Return Rate in Coronary Heart Disease Patients - Syahrir Syahrir; Olliviani Ranuntu; Fatmawati Fatmawati; Nurul Fuady Fitryani A (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Coronary heart disease is one of the diseases that causes death in the world, but these patients must always be controlled or treated regularly so that further complications do not occur or can lead to death. The success of treatment depends on patient compliance itself, where non-adherence causes problems in quality of life. Patients who are not compliant in control will eventually be followed by stopping treatment, this will have an impact on the patient's quality of life. The purpose of this study was to analyze dietary adherence and physical activity with recurrence in coronary heart disease patients. This research is a quantitative study using an analytic survey research method with a cross-sectional study design approach, sampling by total sampling with a total sample of 42 respondents who were outpatients at the heart polyclinic. The results showed the value of dietary adherence (p=0.001), physical activity (p=0.000). So it is said that there is a relationship between dietary adherence and physical activity with recurrence in patients with coronary heart disease at the Heart Polyclinic at the Kolonodale Hospital. It is hoped that people with coronary heart disease will comply more with the recommended dietary patterns and physical activity patterns so that they can reduce the recurrence rate.